A new risk score for ventricular tachyarrhythmia in acute myocardial infarction with preserved left ventricular ejection fraction. Issue 5 (November 2018) - Lee, Seung Hun; Jeong, Myung Ho; Kim, Ju Han; Kim, Min Chul; Sim, Doo Sun; Hong, Young Joon; Ahn, Youngkeun; Chae, Shung Chull; Seong, In Whan; Park, Jong Sun; Chae, Jei Keon; Hur, Seung Ho; et al.
Highlights: 3.5% of acute myocardial infarction patients experienced ventricular tachycardia or fibrillation (VT/VF) even if their left ventricular ejection fraction was preserved. Early VT/VF during hospitalization was associated with a poor prognosis. The VAMIR score could predict VT/VF, and it yielded acceptable discriminant function. The VAMIR score supported the strategies of earlier discharge after revascularization. Abstract: Background: Ventricular tachycardia or fibrillation (VT/VF) is a major cause of sudden cardiac death after acute myocardial infarction (AMI). This study aims to investigate the clinical characteristics and outcomes of VT/VF, to identify the variables associated with VT/VF, and to construct a new scoring system. Methods: Patients with relatively preserved left ventricular ejection fraction (LVEF) (≥40%) included in the Korea Acute Myocardial Infarction Registry-National Institutes of Health registry were enrolled in this study. Among 13, 109 patients in the registry, a total of 10, 334 (78.8%) had relatively preserved LVEF after AMI. Patients were divided into two groups based on whether they experienced life-threatening VT/VF during hospitalization or not. The predictors for VT/VF during hospitalization were assessed. In-hospital mortality and complications were recorded. Results: A total of 358 (3.5%) experienced life-threatening VT/VF. The VT/VF group was at an increased risk of in-hospital mortality (odds ratio 2.99) and cardiac death (odds ratio 3.40). Variables of diagnosis, Killip class, smoking, initial rhythm, left bundle branch block, and LVEF were significant indicators of VT/VF. A new risk score system yielded acceptable discrimination function ( c -statistics = 0.773). Conclusions: Relatively preserved LVEF patients could still be at risk of life-threatening VT/VF, which is related to a poor prognosis during the admission period. This new scoring system can be adopted to stratify the risk of VT/VF.